Innovation through Patents and Intangible Assets: Effects on Growth and Profitability of European Companies - Emanuel Bagna; Enrico Cotta Ramusino; Stefano Denicolai (Journal of Open Innovation: Technology, Market and Complexity, 2021)
Innovation is widely considered one of the most important drivers for firm growth in the contemporary economy. However, the ‘elusive’ as well as heterogeneous nature of innovation has generated a lively debate among scholars with regards to the best metrics to capture its features and effects. Often, this has led to a reliance on R&D and/or patent-related measures. We contribute to this debate by pushing forward the idea that a positive effect of investing in intangibles like patents can’t be taken for granted, since it is significantly influenced by the way a firm’s portfolio of patents is created, assembled, and renewed over time. Starting from a sample of 6677 observations derived from a sample of listed European companies with patents and intangibles booked in their financial statements, this study sheds a new light on how a company creates, composes, and renews over time their portfolio of intangibles, with specific attention on patents. In particular, this contribution discusses the different effects that emerge by making a distinction among different forms of patents, considering two dimensions: broadening vs. deepening investments, and application-specific vs. general purpose investments. We notice that as a company increases investments in intangibles and simultaneously enlarges the breadth of their range of activities, its growth becomes particularly remarkable.